Mapping of agro-ecological zones of Andhra Pradesh through soil-resource data - NAIDU, L G K; REDDY, R S; SAH, K D; BHASKAR, B P; DATTA, D; NIRANJANA, K V; DHANORKAR, B A; SRINIVAS, S; NAGARAJU, M S S; RAY, S K; RAGHUMOHAN, N G (The Indian Journal of Agricultural Sciences, 2013)
An attempt was made to delineate agro-ecological zones of Andhra Pradesh using soil-resource information generated on 1 250 000 scale and rainfall data of 700 rain gauge stations. Length of growing period was computed using both soil-water balance and 0.7 potential evapo-trampiration concept and length of growing periOd map generated. The length of growing period map was superimposed over soil and physiography layer maps through geographical information system and a 22 agro-ecological zones map was generated. The 7 agro-climatie zones map of the Andhra Pradesh Agricultural Umversity prepared under National Agricultural Research Project was superimposed over 22 agro-ecological zones map for comparison and discussion. The length of growing period varied from as low as 70-90 days in Rayalaseema plateau covering about 6% and as high as 210-240 days in the eastern ghats (north) and Delta plains covering about 6 and 2% area of the state respectively. The crop growing season starts ea Iiest in the last week of April in zone 14 of eastern ghats (north) and very late beginning in the first week of August in the southeast coastal plain. Soils in general are dominantly gravelly red, black and deltaic alluvial except in the eastern ghats (north) where they are brown forest soils with high humus content. The 22 agro-ecological ZOnes when compared with the agro-climatic zones indicated that wide variability with respect to physiography, soils and length of growing period and has 2-4 agto- ecological zones within an each agro-climatic zone. Hence there is a need to reorient research programme based on 22 agro-ecological zones for efficient use and conservation of natural resources and agro-teehnology transfer.